PENGEMBANGAN BAHAN AJAR MODUL ILMU PENGETAHUAN ALAM KELAS IV DI SDN 3 REMPUNG - Zalwa Nadia; Donna Boedi Maritasari; Rohini Rohini (PIONIR: JURNAL PENDIDIKAN, 2023)
This study aims to develop a science module as material for learning activities, especially in science subjects using the Borg and Gall research model which consists of 10 steps simplified into 7 steps, namely (1) conducting a needs analysis, (2) planning, (3) initial product development, (4) limited testing, (5) revision of product test results, (6) main product test, (7) final product revision. This study was conducted on class IV students with a total of 22 students. This research and development instrument uses validation sheets and student response questionnaires. The results of the media design expert validation test with a total score of "58" are in the range of 51 < X ≤ 63 with the category "Good". The results of the language expert validation test with a total score of "69" are in the range of X < 63 with the category "Excellent". The results of the material expert validation test with a total score of "72" are in the range of X < 63 with the category "Excellent". The results of the questionnaire of student responses to the validity and effectiveness of the use of the modules developed received an average score of "67.5" and were in the range of X < 63 with the category "Excellent". So that it can be concluded, the science module as material for learning activities is valid and effectively used in the learning process.Keywords:  Module Teaching Materials, Natural Sciences (IPA).